Physicochemical, in vitro antioxidant and cytotoxic properties of water-soluble chitosan-lactose derivatives. (15th November 2019) - Arata Badano, Joaquin; Vanden Braber, Noelia; Rossi, Yanina; Díaz Vergara, Ladislao; Bohl, Luciana; Porporatto, Carina; Falcone, R. Dario; Montenegro, Mariana
Highlights: Water-soluble chitosan-lactose derivatives were synthesized by Maillard reaction. Derivatives with lower Mw, DD and greater solubility than chitosan were obtained. Antioxidant activity of derivatives was greater than or equal to that of chitosan. Derivatives were not cytotoxicity against epithelial cells of the rat ileum IEC-18. Abstract: In this study, water-soluble chitosan (Ch) derivatives were synthesized by the Maillard reaction between Ch and lactose. The Ch derivatives were characterized by FT-IR, 1 H-NMR and SLS to determine their structure, degree of deacetylation (DD), and molecular weight (Mw). The solubility at physiological pH, the in vitro antioxidant activity against hydroxyl radical, anion superoxide radical and ABTS cation radical, and the cytotoxicity against epithelial cells of the rat ileum (IEC-18) were also evaluated. The Maillard reaction, derivatives with lower Mw and DD and greater solubility than Ch were obtained. The biological properties of the derivatives were dependent on the concentration, Mw and DD, with antioxidant activity greater than or equal to that of Ch and non-cytotoxic in a wide range of concentrations. The results indicate that Ch derivatization with lactose produces new water-soluble polysaccharides, with antioxidant activity and non-cytotoxic, which can be used as biomaterials for food and pharmaceutical applications.